2011
DOI: 10.1242/jeb.055871
|View full text |Cite
|
Sign up to set email alerts
|

No apparent ecological trend to the flight-initiating jump performance of five bat species

Abstract: SUMMARYThe jump performance of five insectivorous bat species (Miniopterus schreibersii, Myotis blythii, Myotis capaccinii, Myotis myotis and Rhinolophus blasii) was filmed using a high-speed camera. All study bats jumped using a similar technique, with the wing musculature providing the force. The bats jumped off the wrist joint of their wings, typically with their feet already off the ground. Contrary to expectations, jump performance did not correlate with ecology and was instead strongly determined by body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Indeed, the jump performance of the same study bats (excluding Rhinolophus euryale ) was previously reported by Gardiner and Nudds (Gardiner and Nudds, 2011), but please note that none of the wing induced take-off performance data has been published previously. Miniopterus schreibersii is an aerial hawker feeding in open areas at relatively high altitudes (Norberg and Rayner, 1987).…”
Section: Introductionsupporting
confidence: 52%
See 4 more Smart Citations
“…Indeed, the jump performance of the same study bats (excluding Rhinolophus euryale ) was previously reported by Gardiner and Nudds (Gardiner and Nudds, 2011), but please note that none of the wing induced take-off performance data has been published previously. Miniopterus schreibersii is an aerial hawker feeding in open areas at relatively high altitudes (Norberg and Rayner, 1987).…”
Section: Introductionsupporting
confidence: 52%
“…Alternatively, slowing down and then accelerating back to cruising speed may be essential for some prey capture strategies such as gleaning from both vegetation and water, or for negotiating cluttered environments. Several studies have focussed on take-off performance and accelerating flight in birds (Askew et al, 2001; Berg and Biewener, 2010; Earls, 2000; Jackson and Dial, 2011; Tobalske and Dial, 2000; Tobalske et al, 2004), but far fewer studies have examined bat take-off (Altenbach, 1979; Gardiner and Nudds, 2011; Schutt et al, 1997). In contrast to birds where the wings only play an aerodynamic role, bat wings have two separate functions during a two-phase take-off (Gardiner and Nudds, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations